Composite coating material, method for producing and use thereof

By constructing a piezoelectric-conductive composite coating on the surface of titanium, the problems of insufficient bioelectric activity and ROS generation in titanium-based bone repair materials were solved, thereby improving the electrophysiological microenvironment of titanium implants and enhancing bone repair performance.

CN123038341APending Publication Date: 2026-11-06CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611490290.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-23
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing titanium-based bone repair materials are unable to simulate the bioelectric activity of living bone tissue, resulting in slow recovery of the electrophysiological microenvironment at bone defect sites, affecting cell recruitment, osteogenic differentiation and new bone formation. Furthermore, piezoelectric materials are prone to charge accumulation under ultrasonic stimulation, leading to ROS generation and cell damage.

Method used

A piezoelectric-conductive composite coating, comprising a piezoelectric layer and a conductive hydrogel layer, is constructed on the surface of titanium. The piezoelectric layer generates electrical signals under ultrasonic stimulation, while the conductive hydrogel layer conducts and disperses charges, reducing ROS generation and improving the electrophysiological microenvironment.

Benefits of technology

It improves the bioelectric activity of the titanium implant surface, reduces ROS generation, promotes cell adhesion, proliferation and osteogenic differentiation, improves the bone repair microenvironment, and enhances the electrophysiological compatibility between the implant and the cell interface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123038341A_ABST
    Figure CN123038341A_ABST
Patent Text Reader

Abstract

This invention relates to a composite coating material, its preparation method, and its application, belonging to the field of biomedical materials. The composite coating material of this invention comprises: a surface-modified titanium substrate, and a piezoelectric layer and a conductive hydrogel layer disposed on the surface-modified titanium substrate; the conductive hydrogel layer comprises conductive filler and hydrogel. This invention, through the synergistic effect of its multilayer structure, endows titanium implants with the ability to generate a piezoelectric response under ultrasonic stimulation. Furthermore, the conductive hydrogel layer can conduct and disperse the piezoelectric charge carriers generated by Ce@STO under ultrasonic stimulation, reducing local charge accumulation, thereby reducing ROS generation and cellular oxidative stress induced by charge retention, improving the bioelectric activity of the titanium implant surface, and improving the electrophysiological microenvironment at the implant-cell interface and the bone repair microenvironment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical materials, and relates to a composite coating material, its preparation method and application, specifically a piezoelectric-conductive composite coating material on a titanium surface, its preparation method and application. Background Technology

[0002] Titanium and titanium alloys, due to their excellent mechanical properties, good biocompatibility, and good corrosion resistance, have been widely used in clinical orthopedic implants, dental implants, and bone defect repair materials. In recent years, with the accelerating aging of my country's population and the increase in traumatic events such as traffic accidents and sports injuries, the number of patients with orthopedic diseases and bone defects has been continuously increasing, placing higher demands on the bone repair performance of medical titanium and titanium alloy implant materials. Titanium-based materials can acquire a certain degree of corrosion resistance in bodily fluid environments by forming a stable oxide film on their surface. However, this oxide film also makes the material surface relatively bioinert, making it difficult to actively induce bone marrow mesenchymal stem cell adhesion, proliferation, and osteogenic differentiation, thus limiting the rapid and stable integration of the implant with the surrounding bone tissue.

[0003] Existing technologies typically improve the osteogenic activity of titanium surfaces through methods such as anodizing, micro-arc oxidation, hydroxyapatite coating, bioactive ion doping, or growth factor loading. However, these methods largely rely on passive regulation through surface morphology, chemical composition, or the release of bioactive substances, making it difficult to effectively simulate the bioelectrical activity inherent in living bone tissue. Furthermore, living bone tissue exhibits natural electrophysiological signals during stress and repair. Fractures or large bone defects disrupt the normal local physiological potential, leading to slow recovery of the electrophysiological microenvironment at the bone defect site, which in turn affects cell recruitment, osteogenic differentiation, and new bone formation. In cases of large bone defects, conventional titanium implants cannot provide the natural bioelectrical environment required for bone tissue regeneration, easily causing delayed bone repair, insufficient integration of the implant with the host bone tissue, and increasing the risk of implant loosening or failure.

[0004] Therefore, improving the bioelectric activity of titanium implant surfaces and reshaping the electrophysiological microenvironment of the implant-cell interface has become an important technical issue for enhancing the clinical application performance of titanium-based bone repair materials. Summary of the Invention

[0005] In view of this, the purpose of the present invention is to provide a composite coating material and a method for preparing the same, specifically relating to a piezoelectric-conductive composite coating material for titanium surfaces and a method for preparing the same, as well as the application of the composite coating material in medical implant materials.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A composite coating material comprising: a surface-modified titanium substrate; and a piezoelectric layer and a conductive hydrogel layer disposed on the surface-modified titanium substrate; The conductive hydrogel layer comprises conductive filler and hydrogel.

[0007] In some embodiments, the mass-to-volume ratio of the conductive filler and the hydrogel matrix is ​​(95~110) μg:1mL.

[0008] In some embodiments, the thickness of the piezoelectric layer is 100 nm to 10 μm.

[0009] In some embodiments, the thickness of the conductive hydrogel layer is 10 μm to 200 μm.

[0010] In some embodiments, the surface-modified titanium substrate includes a titanium substrate and micro / nano structures on the surface of the titanium substrate; the titanium substrate includes titanium or a titanium alloy.

[0011] In some embodiments, the conductive filler includes one or more of MXene-like materials, carbon nanomaterials, or conductive polymers.

[0012] In some embodiments, the hydrogel comprises one or more of cross-linked methacrylamide gelatin, gelatin, hyaluronic acid, methacrylamide hyaluronic acid, sodium alginate, polyethylene glycol diacrylate, collagen, fibroin, or chitosan.

[0013] The preparation method of the above-mentioned composite coating material includes the following steps: Provides surface-modified titanium substrates; A piezoelectric layer is formed on the surface-modified titanium substrate; A conductive hydrogel layer is formed on the surface of the piezoelectric layer.

[0014] A titanium implant material, the titanium implant material comprising the above-mentioned composite coating material.

[0015] The above-mentioned composite coating material, or the composite coating material prepared by the above-mentioned preparation method, or the above-mentioned titanium implant material, are used in medical materials.

[0016] The beneficial effects of this invention are as follows: The composite coating material of this invention includes a surface-modified titanium substrate, and a piezoelectric layer and a conductive hydrogel layer disposed on the surface-modified titanium substrate. Specifically, this invention relates to a piezoelectric-conductive composite coating material for titanium surfaces. By constructing a composite electroactive interface of "piezoelectric layer-conductive hydrogel layer", a synergistic effect of piezoelectric signal generation and charge conduction regulation is achieved. Specifically, on the one hand, the piezoelectric layer endows the titanium implant with the ability to generate a piezoelectric response under ultrasonic stimulation. On the other hand, the conductive hydrogel layer formed by the conductive filler and hydrogel matrix improves the interfacial charge conduction and dispersion ability, reduces the excessive accumulation of piezoelectric charge on the material surface, thereby reducing the generation of reactive oxygen species (ROS) under ultrasonic excitation and the risk of cellular oxidative stress caused by it, improving the bioelectric activity of the titanium implant surface, and improving the electrophysiological microenvironment and bone repair microenvironment of the implant-cell interface.

[0017] Other advantages, objectives, and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination, or may be learned from practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. Attached Figure Description

[0018] To make the objectives, technical solutions, and advantages of the present invention clearer, the preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings, wherein: Figure 1 SEM images of TiO2 nanotubes (a, c) and Ce@STO-TiO2 (b, d) prepared in Example 1; Figure 2 SEM images of Ce@STO-TiO2 on titanium surface in Example 1; where (a) is a top view and (b) is a side view; Figure 3 TEM (a) and EDS images (be) of Ce@STO nanoparticles prepared in Example 1; Figure 4 The images show the morphology and elemental characterization results of the Mxene@PDA nanosheets prepared in Example 1 and the GC hydrogel coatings doped with Mxene and Mxene@PDA respectively. (a) is a SEM image of the Mxene@PDA nanosheets; (b) is an EDS elemental analysis diagram of the Mxene@PDA nanosheets; and (c) is a comparison of SEM images of the GC hydrogel coatings doped with Mxene and Mxene@PDA respectively. Figure 5 The results are the evaluation results of the piezoelectric properties of Ce@STO nanoparticles deposited on the TiO2 surface prepared in Example 1; Figure 6Example 1: Results of evaluating the reactive oxygen species (ROS) generation capacity of different materials under ultrasonic stimulation; Figure 7 The results of characterizing the electrical signal response capability of different materials under periodic ultrasound stimulation using current-time (it) curves are shown in Example 1. Figure 8 The results of Micro-CT three-dimensional reconstruction of the femur after implantation of different materials into the rat femur for six weeks in Example 1; Figure 9 SEM results for different materials in Example 2; Figure 10 Electron paramagnetic resonance (EPR) analysis of different materials under ultrasonic stimulation in Example 2; (A) is the EPR spectrum of singlet oxygen (1O2), (B) is the EPR spectrum of superoxide anion (·O2). - (C) is the EPR spectrum of the hydroxyl radical (·OH); Figure 11 The images show Micro-CT three-dimensional reconstructions of bone defect areas in different treatment groups at 8 weeks post-operation for different materials (Ti, CM, and CM-PG) and materials with ultrasound stimulation (Ti+US, CM+US, and CM-PG+US) in Example 2. Detailed Implementation

[0019] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments are only schematic representations of the basic concept of the present invention. Unless otherwise specified, the following embodiments and features can be combined with each other.

[0020] The accompanying drawings are for illustrative purposes only and are schematic diagrams, not actual pictures, and should not be construed as limiting the invention. To better illustrate the embodiments of the invention, some parts in the drawings may be omitted, enlarged, or reduced, and do not represent the actual product dimensions. It is understandable to those skilled in the art that some well-known structures and their descriptions may be omitted in the drawings.

[0021] In the accompanying drawings of the embodiments of the present invention, the same or similar reference numerals correspond to the same or similar components. In the description of the present invention, it should be understood that if terms such as "upper," "lower," "left," "right," "front," and "rear" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, they are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, the terms used to describe positional relationships in the drawings are only for illustrative purposes and should not be construed as limiting the present invention. For those skilled in the art, the specific meaning of the above terms can be understood according to the specific circumstances.

[0022] Piezoelectric materials have broad application prospects in the biomedical field, especially in tissue engineering. This is due to their ability to generate stable, physiologically relevant electrical signals under mechanical or ultrasonic stimulation without requiring an external power source. This unique property makes them ideal candidates for developing self-powered smart implants, which can actively participate in tissue regeneration by simulating the inherent electrophysiological environment of living tissue. However, there are also some problems when using piezoelectric materials as biological implants. For example, piezoelectric materials become polarized and undergo charge separation under external stimuli such as ultrasound. If the interfacial charge cannot be effectively conducted and utilized in a timely manner, it can easily lead to charge accumulation on the material surface or cell interface, thereby inducing the generation of reactive oxygen species (ROS). Excessive ROS can cause oxidative stress in cells around the implant, impairing the adhesion, proliferation, and osteogenic differentiation capacity of bone marrow mesenchymal stem cells, and may exacerbate local inflammatory responses, thus hindering bone tissue regeneration and implant osseointegration.

[0023] Based on this, the present invention provides a composite coating material, the composite coating material comprising: a surface-modified titanium substrate; and a piezoelectric layer and a conductive hydrogel layer disposed on the surface-modified titanium substrate; The conductive hydrogel layer comprises conductive filler and hydrogel.

[0024] In some specific examples, the piezoelectric layer is disposed on the surface of a surface-modified titanium substrate; and the conductive hydrogel layer is disposed on the piezoelectric layer in a direction away from the surface-modified titanium substrate.

[0025] The composite coating material of this invention is a titanium surface piezoelectric-conductive composite coating material. Surface modification of the substrate provides more binding sites and spatial anchoring structures, which is beneficial for improving the loading capacity, distribution uniformity, and interfacial bonding stability of the piezoelectric layer. Under ultrasonic stimulation, the piezoelectric material in the piezoelectric layer can undergo piezoelectric polarization and generate local electrical signals, enabling the titanium implant to acquire ultrasonic-responsive piezoelectric properties. This simulates the mechano-electric coupling microenvironment in living bone tissue, which is beneficial for regulating the electrophysiological behavior of cells surrounding the implant and promoting osteogenic-related responses. Furthermore, the piezoelectric layer can be further composited with a subsequent conductive hydrogel layer, thereby… It provides conditions for the effective conduction of piezoelectric charges and interface regulation; the conductive hydrogel layer also has multiple functions: First, the conductive filler can form a conductive network inside the hydrogel, which helps to conduct and disperse the piezoelectric charges generated by the piezoelectric material under ultrasonic stimulation, reduce local charge accumulation, thereby reducing the risk of ROS generation and cellular oxidative stress induced by charge retention, improving the bioelectric activity of the titanium implant surface, and improving the electrophysiological microenvironment of the implant-cell interface and the bone repair microenvironment; Second, the hydrogel can also provide a flexible water-containing interface similar to the extracellular matrix, improving the cell adhesion, spreading and growth environment.

[0026] In some of these examples, the surface-modified titanium substrate includes a titanium substrate and micro / nano structures on the surface of the titanium substrate; the titanium substrate includes titanium or titanium alloy; the titanium substrate may be, for example, three-dimensionally printed porous titanium, titanium mesh, titanium rod, titanium screw, titanium plate or other titanium materials suitable for bone repair.

[0027] The surface-modified titanium substrate of the present invention forms a rough microstructure on the surface of the titanium substrate, including but not limited to micropores, nanopores, nanorods, nanowires, or other rough hierarchical structures formed through surface treatment; the surface treatment methods include but are not limited to anodizing, micro-arc oxidation, sandblasting and acid etching, alkaline heat treatment, laser etching, electrochemical etching, or plasma treatment. The surface-modified titanium substrate of the present invention can improve the load stability, coating adhesion strength, and cell interface compatibility of piezoelectric materials.

[0028] In some examples, the piezoelectric layer is obtained by applying a piezoelectric material to the surface-modified titanium substrate; the application method includes, but is not limited to, electrodeposition, hydrothermal synthesis, sol-gel, spin coating, spraying, dip coating, electrophoretic deposition, physical vapor deposition, or chemical deposition.

[0029] In some examples, the piezoelectric material is a class of materials possessing piezoelectric response and biocompatibility. The piezoelectric material includes one or more of modified or unmodified inorganic piezoelectric materials and piezoelectric polymers, such as, but not limited to, one or more of strontium titanate, barium titanate, calcium titanate, magnesium titanate, zinc oxide, polyvinylidene fluoride, and their copolymers, as well as composites of various inorganic piezoelectric materials. Modification methods include doping, with doping elements including, but not limited to, cerium, strontium, calcium, barium, lanthanum, magnesium, and zinc. In some specific examples, the piezoelectric material is selected from cerium-doped strontium titanate nanoparticles (Ce@STO) or calcium magnesium titanate (Ca,Mg)TiO3.

[0030] In some examples, the thickness of the piezoelectric layer is 100 nm to 10 μm; preferably 500 nm to 1 μm.

[0031] In some examples, the conductive hydrogel layer is formed by coating a conductive filler with a hydrogel matrix onto the surface of the piezoelectric layer and then crosslinking it in situ. Understandably, the hydrogel matrix undergoes a crosslinking reaction to form the hydrogel. Hydrogels can provide cells with a flexible, hydrophilic, and conductive biological interface, which is beneficial for cell adhesion, proliferation, and osteogenic differentiation.

[0032] In some examples, the mass-to-volume ratio of the conductive filler to the hydrogel matrix is ​​(95~110) μg:1mL; preferably, the mass-to-volume ratio of the conductive filler to the hydrogel matrix is ​​100 μg:1mL.

[0033] In some examples, the conductive filler comprises one of MXene-like materials, carbon nanomaterials, or conductive polymers. One or more types; specifically, the MXene-type material includes modified or unmodified MXene; the carbon nanomaterial includes reduced graphene oxide, graphene, or carbon nanotubes; the conductive polymer material includes poly(3,4-ethylenedioxythiophene) (PEDOT), poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) (PEDOT:PSS), or polypyrrole, etc.; in some specific examples, the modified MXene includes, but is not limited to, modification with polydopamine (PDA), tannic acid, polyethyleneimine, silane coupling agents, chitosan, etc.; in some more specific examples, the conductive filler is selected from polydopamine-modified MXene (MXene@PDA) or PEDOT:PSS.

[0034] In some examples, the hydrogel comprises one or more of cross-linked methacrylamide gelatin, gelatin, hyaluronic acid, methacrylamide hyaluronic acid, sodium alginate, polyethylene glycol diacrylate, collagen, fibrin, or chitosan; understandably, the hydrogel is a product formed by cross-linking a hydrogel matrix; the hydrogel matrix comprises one or more of methacrylamide gelatin, gelatin, hyaluronic acid, methacrylamide hyaluronic acid, sodium alginate, polyethylene glycol diacrylate, collagen, fibrin, or chitosan; in some specific examples, the hydrogel matrix is ​​a composite hydrogel of methacrylamide gelatin and chitosan (GelMA / CS). The conductive hydrogel layer formed by the conductive filler and hydrogel of the present invention can improve the dispersibility, interfacial bonding, and aqueous phase stability of the conductive filler.

[0035] In some examples, the thickness of the conductive hydrogel layer is 10 μm to 200 μm, preferably 20 μm to 100 μm. The present invention can control the thickness and uniformity of the conductive hydrogel layer by adjusting the concentration of the hydrogel matrix precursor solution, the coating amount, the spin coating speed, the spin coating time, and the crosslinking conditions.

[0036] In some specific examples, the surface-modified substrate of the composite coating material is a TiO2 nanotube array generated in situ on the surface of a titanium substrate, the piezoelectric layer is a Ce@STO piezoelectric nanoparticle layer, and the conductive hydrogel layer is a Mxene@PDA-doped GelMA / CS conductive hydrogel layer. This invention forms a piezoelectric-conductive composite electroactive coating by sequentially constructing a TiO2 nanotube array, a Ce@STO piezoelectric nanoparticle layer, and a Mxene@PDA-doped GelMA / CS conductive hydrogel layer on the surface of a titanium implant. Compared with existing single piezoelectric coatings, the TiO2 nanotube array anchors the Ce@STO piezoelectric nanoparticles, improving the loading stability and distribution uniformity of the Ce@STO nanoparticles; Ce@STO can generate piezoelectric signals under ultrasonic stimulation to simulate the bioelectric microenvironment of natural bone tissue; the Mxene@PDA conductive hydrogel layer can conduct and disperse the charge generated by the piezoelectric layer, reducing local charge accumulation, thereby reducing the risk of excessive ROS generation and cellular oxidative stress under ultrasonic excitation. Meanwhile, PDA modification can improve the dispersibility, interfacial binding, and antioxidant stability of Mxene in hydrogels, while GelMA / CS hydrogels provide cells with a flexible, hydrophilic, and conductive biological interface, which is beneficial for cell adhesion, proliferation, and osteogenic differentiation. Therefore, this invention can endow titanium implants with ultrasonically responsive piezoelectric activity while improving the problems of insufficient charge conduction, ROS-induced oxidative damage, and poor interfacial cell compatibility of existing piezoelectric coatings, thereby improving the bone repair and osseointegration performance of titanium implants.

[0037] In some other specific examples, the surface-modified substrate of the composite coating material is an alkaline-thermally treated porous micro / nano structured titanium substrate, the piezoelectric layer is a magnesium calcium titanate (Ca,Mg)TiO3 piezoelectric coating, and the conductive hydrogel layer is a PEDOT:PSS / GEL conductive coating.

[0038] The present invention also provides a method for preparing the above-mentioned composite coating material, comprising the following steps: S100: Provides a surface-modified titanium substrate, which has micro / nano structures on the titanium substrate.

[0039] The surface-modified titanium substrate of the present invention forms a rough microstructure on the surface of the titanium substrate, including but not limited to micropores, nanopores, nanorods, nanowires, or other rough hierarchical structures formed through surface treatment; the surface treatment methods include but are not limited to anodizing, micro-arc oxidation, sandblasting and acid etching, alkaline heat treatment, laser etching, electrochemical etching, or plasma treatment. The surface-modified titanium substrate of the present invention can improve the load stability, coating adhesion strength, and cell interface compatibility of piezoelectric materials.

[0040] In some specific examples, the surface-modified titanium substrate is anodized to form an in-situ TiO2 nanotube array on the surface of the titanium substrate. The TiO2 nanotubes have an inner diameter of 20 nm to 150 nm, a wall thickness of 5 nm to 30 nm, and a length of 0.2 μm to 2 μm; preferably, the TiO2 nanotubes have an inner diameter of 50 nm to 120 nm and a length of 0.5 μm to 1 μm.

[0041] More specifically, the in-situ formation of TiO2 nanotube arrays on the surface of a titanium substrate includes the following steps: An anodizing electrolyte was prepared by mixing glycerol, ammonium fluoride, and water; anodizing was performed in the anodizing electrolyte using a titanium substrate as the working electrode and a platinum sheet as the counter electrode. More specifically, the mass-to-volume ratio of the ammonium fluoride, the glycerol, and the water was 1 g : (45~60) mL : (45~60) mL; the anodizing voltage was 10 V~25 V; and the anodizing time was 1 h~4 h. In some specific examples, the titanium substrate is pretreated by cutting the titanium foil to a predetermined size and then ultrasonically cleaning it sequentially in acetone, anhydrous ethanol, and deionized water for 10 to 20 minutes each time to remove oil, particles, and other impurities from the surface of the titanium foil. After cleaning, it is rinsed with deionized water and dried with inert gas or naturally to obtain the pretreated titanium substrate. In some specific examples, after anodizing, purification and drying steps are also included. Purification includes immersion in ethylene glycol to remove residual electrolyte and unstable reaction products from the surface, and sequential cleaning with deionized water and ethanol to further remove surface impurities.

[0042] This invention employs in-situ anodic oxidation to form TiO2 nanotube arrays, which have regular micro-nano structures. This provides more bonding sites and spatial anchoring structures for the subsequent deposition of piezoelectric materials, which is beneficial to improving the loading, distribution uniformity, and interfacial bonding stability of the piezoelectric particle layer. At the same time, the TiO2 nanotube structure can also improve the surface roughness and specific surface area of ​​titanium, which is beneficial to improving the bonding strength between the subsequent composite coating and the titanium substrate.

[0043] In some other specific examples, the surface-modified titanium substrate is a porous micro / nano structure titanium substrate formed by alkaline thermal treatment; optionally, the alkaline thermal treatment is carried out by mixing pure titanium with a strong alkaline solution and then performing an alkaline thermal reaction in a high-pressure reactor; further optionally, the strong alkaline solution includes NaOH solution; the temperature of the alkaline thermal reaction is 50℃~70℃; and the time of the alkaline thermal reaction is 10h~14h.

[0044] The surface-modified titanium substrate of this invention is not limited to TiO2 nanotube arrays formed by anodic oxidation and porous micro / nano structures formed by alkaline thermal treatment. Micropores, nanopores, nanorods, nanowires, or rough hierarchical structures can also be formed through micro-arc oxidation, sandblasting and acid etching, laser etching, electrochemical etching, or plasma treatment. Any method that can improve the piezoelectric particle loading stability, coating bonding strength, and cell interface compatibility can be used as an alternative. S200: A piezoelectric layer is formed on the surface-modified titanium substrate.

[0045] In some of these examples, piezoelectric material is deposited on the surface-modified titanium substrate to form the piezoelectric layer.

[0046] Understandably, deposition methods include, but are not limited to, electrodeposition, hydrothermal synthesis, sol-gel, spin coating, spraying, dip coating, electrophoretic deposition, physical vapor deposition, or chemical deposition. As long as a stable piezoelectric response layer can be formed on the surface of the titanium substrate and a local electrical signal can be generated under external mechanical stimulation, it is an alternative solution.

[0047] In some of these examples, piezoelectric layers were prepared by electrodeposition; the electrodeposition voltage was 2V to 3V; and the electrodeposition time was 5 min to 15 min.

[0048] In some examples, the piezoelectric material is cerium-doped strontium titanate nanoparticles (Ce@STO). As an example, when the piezoelectric material is cerium-doped strontium titanate nanoparticles, the preparation of the piezoelectric layer includes the following steps S210 to S240: S210: Prepare the main solution by mixing strontium nitrate, potassium chloride, and cerium nitrate in an acidic solution; Optionally, the molar ratio of strontium nitrate, potassium chloride and cerium (III) nitrate is (0.9-2.1):(0.9-2.1):(0.005-0.03).

[0049] Optionally, the acid solution is a nitric acid solution with a pH of 0.5 to 1.5.

[0050] S220: Titanium oxysulfate and nitric acid are mixed to prepare a titanium-containing precursor solution; Optionally, the molar ratio of titanium oxysulfate to nitric acid is (2~5):1. Optionally, the concentration of nitric acid is (0.05~0.20) mol / L, preferably 0.10 mol / L.

[0051] S230: Mix the main solution, the titanium-containing precursor solution and the hydrogen peroxide solution to prepare the electrodeposition solution for cerium-doped strontium titanate nanoparticles; S240: Using a surface-modified titanium substrate as the working electrode and a platinum sheet as the counter electrode, electrodeposition is performed in the electrodeposition solution of the cerium-doped strontium titanate nanoparticles, followed by washing and drying.

[0052] In some specific examples, the electrodeposition voltage is 2 V to 3 V; the electrodeposition time is 5 min to 15 min.

[0053] In other examples, the piezoelectric material is calcium magnesium titanate (Ca,Mg)TiO3.

[0054] In other specific examples, the preparation of a magnesium calcium titanate (Ca,Mg)TiO3 (CM) piezoelectric coating includes the following steps: A (Ca,Mg)TiO3 piezoelectric coating was deposited on a surface-modified titanium substrate by electrodeposition using a mixed aqueous solution of sodium hydroxide, magnesium salt, and calcium salt.

[0055] In some other specific examples, the molar ratio of sodium hydroxide to magnesium salt and calcium salt is 1:(0.1~0.25):(0.1~0.25); preferably, the molar ratio of sodium hydroxide to magnesium salt and calcium salt is 1:0.125:0.125.

[0056] In other specific examples, the electrodeposition temperature is 60°C to 80°C; preferably 70°C; the electrodeposition time is 1 min to 3 min; preferably 2 min; and the electrodeposition voltage is 1 V to 3 V; preferably 2 V.

[0057] This invention involves depositing a piezoelectric layer on a surface-modified substrate. The piezoelectric material generates electrical signals upon external stimulation, enabling the titanium implant to acquire ultrasound-responsive piezoelectric properties. Under ultrasound stimulation, the piezoelectric material undergoes piezoelectric polarization and generates local electrical signals, thereby mimicking the mechano-electric coupling microenvironment in living bone tissue. This facilitates the regulation of the electrophysiological behavior of cells surrounding the implant and promotes osteogenic responses. External stimulation methods include low-intensity pulsed ultrasound, mechanical vibration, periodic pressure, in vivo motion loads, external mechanical loading, or other mechanical stimulation methods that can induce the piezoelectric material to generate electrical signals.

[0058] S300: A conductive hydrogel layer is formed on the surface of the piezoelectric layer.

[0059] Specifically, a conductive precursor solution comprising a matrix of conductive fillers and hydrogels is applied to the piezoelectric layer, causing the hydrogel matrix to undergo a crosslinking reaction to form the conductive hydrogel layer.

[0060] In some examples, the conductive precursor solution also includes an initiator; specifically, the initiator includes lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP). In this invention, under the action of a photoinitiator, the matrix of the hydrogel in the conductive precursor solution undergoes a cross-linking reaction to form a conductive hydrogel layer, which has multiple functions: First, conductive fillers such as Mxene@PDA nanosheets can form a conductive network inside the hydrogel, which helps conduction and dispersion; piezoelectric materials such as Ce@STO generate piezoelectric charges under ultrasonic stimulation, reducing local charge accumulation, thereby reducing ROS generation and cellular oxidative stress induced by charge retention; second, the formed hydrogel can also provide a flexible water-containing interface similar to the extracellular matrix, improving the cell adhesion, spreading, and growth environment.

[0061] The crosslinking reactions of this invention include, but are not limited to, ultraviolet light crosslinking, visible light crosslinking, ionic crosslinking, pH-induced gelation, thermosensitive gelation, enzymatic crosslinking, or multiple crosslinking methods.

[0062] In some examples, when a conductive precursor solution comprising a matrix including conductive fillers and hydrogels is applied to the piezoelectric layer step, the application method includes, but is not limited to, spin coating, drop coating, dip coating, spray coating, molding, layer-by-layer self-assembly, in-situ gelation, or 3D printing.

[0063] In some specific examples, the conductive filler is PDA-modified Mxene nanosheets (Mxene@PDA).

[0064] In some specific examples of this invention, Mxene@PDA is used as a conductive filler, resulting in a polydopamine coating layer with adhesive and protective properties on the surface of Mxene nanosheets. On one hand, this PDA coating layer improves the dispersion stability of Mxene in the hydrogel precursor solution, reduces nanosheet aggregation, and enhances the interfacial bonding between Mxene and the hydrogel matrix (such as GelMA / CS). On the other hand, the PDA coating layer can, to some extent, isolate or weaken the effects of moisture and dissolved oxygen on the Mxene surface, thereby reducing the oxidative degradation rate of Mxene in aqueous environments and improving its structural and conductive stability in the hydrogel system. Simultaneously, the active groups such as hydroxyl and amino groups on the PDA surface enhance the interaction between the conductive filler and the hydrogel network, forming a more stable, continuous, and water-resistant conductive pathway, providing a foundation for subsequent conduction and dispersion of the charge generated by the piezoelectric layer. Therefore, the present invention uses PDA modification, which helps to enhance the interaction between the conductive filler Mxene and the hydrogel matrix, improve the stability and dispersibility of the conductive filler in the hydrogel, and enable the coating to have good interfacial compatibility while maintaining conductivity.

[0065] In some specific examples, the hydrogel matrix is ​​a composite hydrogel (GelMA / CS) of methacrylamide gelatin (GelMA) and deacetylated chitosan (CS); more specifically, the preparation of the GelMA / CS includes the following steps: dissolving GelMA in PBS solution to prepare a GelMA solution with a mass concentration of 10 w / w%; dissolving deacetylated chitosan (CS) in acetic acid solution with a volume fraction of 1% to prepare a CS solution with a mass concentration of 1%. The GelMA solution and the CS solution are then mixed at a volume ratio of 4:1 to obtain a GelMA / CS mixed hydrogel precursor solution.

[0066] In some other specific examples, the conductive filler is PEDOT:PSS; and the matrix of the hydrogel is gelatin.

[0067] A titanium implant material, the titanium implant material comprising the above-mentioned composite coating material.

[0068] The above-mentioned composite coating material, or the composite coating material prepared by the above-mentioned preparation method, or the above-mentioned titanium implant material, are used in medical materials.

[0069] In some of these examples, the medical materials include, but are not limited to, clinical orthopedic implants, dental implants, and materials for repairing bone defects.

[0070] The following are specific embodiments. Unless otherwise specified, the instruments, reagents, and materials involved in these embodiments are all conventional instruments, reagents, and materials already existing in the prior art and can be obtained through legitimate commercial channels. Unless otherwise specified, the experimental methods and detection methods involved in the following embodiments are all conventional experimental methods and detection methods already existing in the prior art.

[0071] Example 1 Step 1: Fabrication of TiO2 nanotube arrays on titanium substrate surface 500 mL of deionized water, 500 mL of glycerol, and 10 g of dried ammonium fluoride were added to a container and stirred thoroughly until the ammonium fluoride was completely dissolved to obtain a homogeneous anodic oxidation electrolyte. A pre-treated titanium implant (after polishing and cleaning) was used as the working electrode, and a platinum sheet as the counter electrode. Connected to a DC power supply, anodizing was performed at 20 V for 1 h to form an in-situ TiO2 nanotube array on the surface of the titanium implant. After anodizing, the titanium implant was removed and immersed in ethylene glycol for 10 min to remove residual electrolyte and unstable reaction products. It was then washed sequentially with deionized water and ethanol to further remove surface impurities, and finally dried for later use.

[0072] Step 2: Fabrication of the piezoelectric layer (1) Preparation of electrodeposition solution for cerium-doped strontium titanate nanoparticles (Ce@STO) Take 270 mL of deionized water, add an appropriate amount of nitric acid and stir until homogeneous, adjusting the pH of the solution to approximately 1. Then add 3.17 g of strontium nitrate, 1.12 g of potassium chloride, and 78 mg of cerium nitrate hexahydrate (III), stirring until completely dissolved to obtain a main solution containing strontium, potassium, and cerium ions. Separately, take 1.176 g of titanium oxysulfate and dissolve it in 20 mL of 0.1 M dilute nitric acid to obtain a titanium-containing precursor solution. Slowly add the titanium-containing precursor solution to the above main solution, and add 0.5 mL of hydrogen peroxide to reduce titanium ion hydrolysis and improve the stability of the deposition solution. Then add deionized water to bring the volume to 300 mL and stir thoroughly to obtain the Ce@STO nanoparticle electrodeposition solution.

[0073] (2) Electrodeposition of Ce@STO nanoparticles on titanium surface The TiO2 nanotube-modified titanium implant obtained in step 1 was used as the working electrode, and a platinum sheet was used as the counter electrode. The implant was placed in the Ce@STO electrodeposition solution obtained in step (1), connected to a DC power supply, and electrodeposited at 2 V for 10 min to deposit cerium-doped strontium titanate nanoparticles onto the surface of the TiO2 nanotubes and its surrounding area. After electrodeposition, the sample was removed, gently washed with deionized water to remove unbound ions and particles from the surface, and then dried to obtain the titanium implant with Ce@STO nanoparticles modified on its surface.

[0074] Step 3: Prepare the conductive hydrogel layer (1) Preparation of Mxene@PDA nanosheets (a) Preparation of monolayer Mxene nanosheets LiF, HCl, and deionized water were added to a corrosion-resistant reaction vessel in a mixture of 30 mL of 12 M hydrochloric acid, 10 mL of deionized water, and 2 g of LiF. After thorough mixing, the mixture was heated to 35°C. Subsequently, 2 g of Ti3AlC2 raw material was slowly added to the above-mentioned mixed etching solution in small batches. The mixture was magnetically stirred at 600 rpm for 12 h to remove the Al layer from Ti3AlC2 and obtain multilayer Ti3C2T. x Mxene. After the reaction was completed, the reaction product was collected by centrifugation and repeatedly washed and centrifuged with deionized water until the pH of the supernatant was close to neutral.

[0075] Subsequently, LiCl intercalation was performed: 2 g of solid LiCl was dissolved in 40 mL of deionized water to obtain a LiCl intercalation solution; this solution was then added to the Ti3C2T obtained by centrifugation. x In the Mxene precipitate, the mixture was magnetically stirred at 500 rpm for 12 h at room temperature to allow Li to precipitate. + Fully insert between Mxene layers.

[0076] After the intercalation reaction, the mixture was centrifuged, the supernatant was discarded, and fresh deionized water was added for redispersibility, followed by further centrifugation and washing. As washing and dispersion proceeded, the system gradually transformed from a precipitate to a homogeneous black dispersion. The resulting dispersion was then transferred to a three-necked flask and subjected to ultrasonic exfoliation for 15 min under nitrogen protection and an ice bath to obtain monolayer or few-layer Mxene nanosheet dispersions. After ultrasonication, the dispersion was centrifuged at low speed, and the upper homogeneous dispersion was collected, which was the monolayer Mxene nanosheet dispersion. The obtained dispersion, after appropriate dilution, was dark green or deep green, indicating that the Mxene nanosheets had good dispersibility. Finally, the upper dispersion was freeze-dried to obtain lyophilized Mxene nanosheets.

[0077] (b) Preparation of Mxene@PDA nanosheets Weigh the freeze-dried Mxene nanosheets prepared in step (a) above, add them to deionized water to prepare a Mxene nanosheet dispersion of about 1 mg / mL, and perform appropriate ultrasonic treatment under nitrogen protection to fully disperse them and form a stable monolayer or few-layer Mxene nanosheet dispersion.

[0078] Separately, dopamine hydrochloride was dissolved in deionized water to prepare a dopamine hydrochloride solution of approximately 0.5 mg / mL. Subsequently, the Mxene nanosheet dispersion and the dopamine hydrochloride solution were mixed at a volume ratio of 1:1 and stirred at room temperature for 4 h under nitrogen protection to allow dopamine molecules to be fully adsorbed onto the surface of the Mxene nanosheets and undergo a self-polymerization reaction, thereby forming a polydopamine coating layer on the Mxene surface.

[0079] After the reaction was completed, the product was collected by centrifugation, and the precipitate was washed five times with deionized water to remove unreacted dopamine monomers and byproducts. Finally, the washed precipitate was freeze-dried to obtain Mxene@PDA nanosheets.

[0080] (2) Preparation of Mxene-doped hydrogel precursor solution GelMA (methacrylamide gelatin) was dissolved in PBS solution to prepare a 10% (w / w) GelMA solution; CS was dissolved in 1% (v / v) acetic acid solution to prepare a 1% (w / w) CS solution. The GelMA and CS solutions were then mixed at a volume ratio of 4:1 to obtain a GelMA / CS mixed hydrogel precursor solution.

[0081] Add the Mxene@PDA nanosheets prepared in step 3 (1) to the above mixed hydrogel precursor solution to make the final concentration of Mxene@PDA nanosheets 100 μg / mL, and add 0.1% LAP by mass of the precursor solution as a photoinitiator. Stir thoroughly to make the Mxene@PDA nanosheets uniformly dispersed in the hydrogel precursor solution to obtain the Mxene@PDA doped hydrogel precursor solution GelMA / CS-Mxene@PDA.

[0082] (3) Piezoelectric-conductive composite electroactive coating on titanium surface Take the titanium implant containing Ce@STO nanoparticles prepared in step 2 above, drop the Mxene@PDA doped hydrogel precursor solution GelMA / CS-Mxene@PDA onto its surface, and place it on a spin coater for spin coating treatment, so that the hydrogel precursor solution is evenly spread on the Ce@STO modified titanium surface to form a continuous hydrogel precursor thin layer.

[0083] Subsequently, UV irradiation for 2 min induced photocrosslinking and initial gelation of the GelMA. After UV crosslinking, the sample was immersed in 0.1 M NaOH solution for 10 min. This alkali treatment promoted CS gelation and neutralized residual acidic components in the system, further stabilizing the hydrogel layer. After treatment, the sample was removed and thoroughly washed with sterile deionized water or PBS to remove residual NaOH and unreacted components, thus obtaining a piezoelectric-conductive composite electroactive coating on the titanium surface.

[0084] Example 2 Step 1: Fabrication of micro / nano structures modified on titanium substrate surface (1) Place the cut pure titanium sheet in acetone, anhydrous ethanol and deionized water in sequence, and ultrasonically clean for 15 minutes each to remove surface oil and impurities. Dry after cleaning and set aside.

[0085] (2) Alkali heat treatment of pure titanium. First, a 5 mol / L NaOH solution was prepared by weighing 40 g of NaOH and dissolving it in 200 mL of deionized water, and stirring magnetically until completely dissolved. Then, the resulting solution was transferred to a polytetrafluoroethylene-lined high-pressure reactor, and the pretreated titanium sheet was vertically immersed in the alkaline solution. After sealing the reactor, it was placed in a forced-air drying oven and reacted at 60 °C for 12 h. After the reaction was completed, it was naturally cooled to room temperature, the sample was taken out, and repeatedly rinsed with deionized water until neutral. After drying, a porous micro / nano-structured titanium substrate with alkaline heat treatment was obtained.

[0086] Step 2: Fabrication of the piezoelectric layer (1) Preparation of electrodeposition solution for magnesium calcium titanate (Ca,Mg)TiO3 (CM) piezoelectric coating First, prepare the electrolyte by weighing 8.00 g NaOH, 3.56 g magnesium acetate, and 3.95 g calcium acetate, adding them to 100 mL of deionized water, and stirring magnetically until completely dissolved. At this point, the concentration of NaOH in the electrolyte is 2 M, and the concentrations of magnesium acetate and calcium acetate are both 0.25 M.

[0087] (2) Electrodeposition of (Ca,Mg)TiO3 nanoparticles on titanium surface An in-situ (Ca,Mg)TiO3 piezoelectric coating was grown on an alkaline-thermally treated titanium substrate using anodic electrodeposition. During electrodeposition, a platinum sheet was used as the cathode, and the alkaline-thermally treated titanium sheet was used as the anode, both immersed in an electrolyte. To optimize the surface morphology and piezoelectric properties of the coating, single-factor experiments were conducted to compare parameters such as deposition temperature, voltage, and time. The optimal preparation conditions were determined to be a deposition temperature of 70 °C, a voltage of 2 V, and a deposition time of 2 min. After deposition, the sample was removed, ultrasonically cleaned for 30 s, rinsed with deionized water, and dried for later use.

[0088] Step 3: Prepare the conductive hydrogel layer (1) Solution preparation for PEDOT:PSS / GEL (PG) conductive coating PEDOT:PSS composite solution: Mix PEDOT:PSS dispersion, dimethyl sulfoxide, and anhydrous ethanol at a volume ratio of 20:1:5. After mixing, stir on a magnetic stirrer until the solution is homogeneous. The prepared solution is ready for use. Dimethyl sulfoxide is used to improve the conductivity of PEDOT:PSS, and anhydrous ethanol is used to improve the spreadability and volatility of the solution.

[0089] Gel solution: Weigh 0.1 g of gelatin powder, add it to 50 mL of deionized water, and stir in a 60℃ water bath until completely dissolved to prepare a gelatin solution with a mass fraction of 0.2 wt%.

[0090] (2) PEDOT:PSS / GEL (PG) conductive coating spin-coating film A PEDOT:PSS layer and a gel layer were sequentially spin-coated onto the surface of a (Ca,Mg)TiO3 substrate using a spin coater. The spin-coating program was set to two steps. The first step was at 800 rpm for 6 seconds to ensure uniform spread of the solution on the substrate surface. The second step was at 3000 rpm for 20 seconds to form a more uniform thin film.

[0091] First, the prepared PEDOT:PSS composite solution was dropped onto the surface of a (Ca,Mg)TiO3 substrate and spin-coated according to the procedure described above. After spin-coating, the sample was heated at 120℃ for 10 min to remove residual solvent and improve the stability of the PEDOT:PSS film. After the sample cooled to room temperature, a Gel solution was dropped onto the surface of the PEDOT:PSS layer, and a second spin-coating was performed using the same spin-coating parameters. After spin-coating, the sample was allowed to air dry to obtain a stable (Ca,Mg)TiO3@PEDOT:PSS / GEL (CM-PG) composite coating.

[0092] Performance Characterization (1) Performance testing and characterization in Example 1 The surface-modified titanium substrate prepared in step 1, the Ce@STO-TiO2 piezoelectric coating (Ce@STO) prepared in step 2, and the GC / Mxene@PDA conductive coating prepared in step 3 of Example 1 were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and energy dispersive X-ray spectroscopy (EDS).

[0093] Figure 1 SEM images of the surface-modified titanium substrate with TiO2 nanotubes on the titanium surface and the surface-modified titanium substrate with piezoelectric layer Ce@STO-TiO2 prepared in Example 1, wherein... Figure 1 (a) and Figure 1 (c) shows the SEM image of TiO2 nanotubes. Figure 1 (b) and Figure 1 (d) shows the SEM image of Ce@STO-TiO2, based on Figure 1 The characterization results show that Ce@STO nanoparticles are mainly distributed in a dotted or ring-shaped pattern along the edge of the TiO2 nanotube opening, indicating that the TiO2 nanotube structure can provide effective attachment sites for the deposition of Ce@STO nanoparticles.

[0094] Figure 2 This is a SEM image of the Ce@STO-TiO2 surface on titanium 10 min after electrodeposition. Figure 2 (a) The top view shows that the surface of the TiO2 nanotube array is covered with a large number of fine particles. The particles are evenly distributed and deposited along the tube opening and around the tube wall, making the surface present a rougher granular morphology. Figure 2 (b) The side view shows that the vertically aligned nanotube structure is intact, with Ce@STO nanoparticles attached to the surface and outer region of the nanotubes.

[0095] Figure 3 The TEM (a) and EDS (be) elemental mapping results of Ce@STO nanoparticles prepared in Example 1 are shown below. Figure 3 It can be seen that Ce@STO particles have a nanoscale morphology and can form local clusters; the elemental signals of Ti, O, Sr and Ce have a good spatial correspondence with the particle morphology region, proving that cerium-doped strontium titanate nanoparticles have been successfully constructed.

[0096] Figure 4 The morphology and elemental characterization results of the MXene@PDA nanosheets and Mxene and Mxene@PDA-doped GC hydrogel coatings prepared in Example 1 are shown in (a) SEM image of Mxene@PDA nanosheets; (b) EDS elemental analysis diagram of Mxene@PDA nanosheets; and (c) comparison of SEM images of the Mxene-doped GC hydrogel coating GC / Mxene (denoted as GC / Mx gel) and the Mxene@PDA-doped GC hydrogel coating GC / Mxene@PDA (denoted as GC / Mx@PDA gel). Figure 4 (a) and Figure 4 (b) The results show that MXene@PDA maintains a typical layered nanostructure, and N element was detected by EDS, indicating that PDA was successfully modified on the MXene surface; Figure 4(c) SEM results show that the pore walls of GC / Mxene@PDA gel are rougher, exhibiting a wrinkled and sheet-like stacked structure. The nanosheets are well embedded and combined in the GC hydrogel network, while the pore walls of GC / Mxene gel are relatively flat and smooth.

[0097] Figure 5 The piezoelectric performance evaluation results of Ce@STO nanoparticles deposited on the TiO2 surface prepared in step 2 of Example 1 are as follows: Figure 5 It can be seen that the Ce@STO sample exhibits a significant local piezoelectric response signal under an applied bias voltage. The phase signal flips with the voltage, and the amplitude signal shows typical piezoelectric response characteristics, indicating that it has polarization behavior that can be controlled by an external electric field.

[0098] Figure 6 This is the evaluation result of the reactive oxygen species (ROS) generation capacity of different materials under ultrasonic stimulation in Example 1. Among them, (a) represents singlet oxygen. 1 O2 - (a) The ability to generate hydroxyl radicals (·OH); (b) The ability to generate superoxide anions (·O2). - The generation capacity; Ti represents the unmodified titanium substrate, and the Ti group has a lower ROS level; Ce@STO is the piezoelectric particle prepared in step 2 of Example 1, and the Ce@STO group can significantly promote the generation of singlet oxygen, hydroxyl radicals and superoxide anions; Ce@STO / gel is the piezoelectric-conductive composite electroactive coating on the titanium surface prepared in step 3 of Example 1, and the ROS signal of the Ce@STO / gel composite coating group is significantly reduced, indicating that the MXene@PDA conductive hydrogel layer can effectively conduct and disperse the charge generated by the piezoelectric layer, reduce local charge accumulation, and reduce the risk of oxidative stress.

[0099] Figure 7 The results of the current-time (it) curves used in Example 1 to characterize the electrical signal response capabilities of different materials under periodic ultrasonic stimulation are as follows: The titanium group (Ti) only produced weak current fluctuations; the Ce@STO piezoelectric layer group showed a regular transient current response under periodic ultrasonic stimulation, with an amplitude of approximately 592.99 nA; the Ce@STO-gel composite coating group still maintained a stable electrical signal output of approximately 491.45 nA, indicating that the composite coating can improve the problem of local charge accumulation while retaining the piezoelectric stimulation effect.

[0100] Figure 8The results show the 3D reconstruction results of different materials using Micro-CT six weeks after implantation. Without ultrasound treatment (-US), the Ce@STO / gel group showed a more pronounced ring-shaped new bone formation compared to the Ti and Ce@STO groups. After low-intensity pulsed ultrasound treatment (+US: treatment conditions were 1 MHz frequency, 0.2 W intensity, and 50% duty cycle for cell experiments; 1 MHz frequency, 0.3 W intensity, and 50% duty cycle for animal experiments), overall bone formation was enhanced in all groups, with the Ce@STO / gel+US group showing the most significant effect, exhibiting a continuous and dense new bone surrounding structure. These results indicate that the Ce@STO / gel composite electroactive coating can promote new bone formation around the implant, and ultrasound stimulation further enhances the bone regeneration effect.

[0101] (2) Performance testing and characterization in Example 2 The modified titanium substrate Ti, magnesium calcium titanate (Ca,Mg)TiO3 piezoelectric coating (CM) prepared in Example 2 and the (Ca,Mg)TiO3@PEDOT:PSS / GEL (CM-PG) composite coating prepared in step 3 were characterized in terms of structure and performance.

[0102] Figure 9 SEM results for Ti, titanium surface (Ca,Mg)TiO3 nanoparticles, and (Ca,Mg)TiO3@PEDOT:PSS / GEL composite coating are shown. Ti represents the unmodified titanium substrate, CM represents the (Ca,Mg)TiO3 nanoparticles on the titanium surface, and CM-PG represents the (Ca,Mg)TiO3@PEDOT:PSS / GEL composite coating. Figure 9 As can be seen, the Ti group shows that the unmodified Ti surface is relatively smooth and dense, with no obvious special surface structures. In contrast, the CM group shows obvious roughening characteristics, with a large number of uniformly distributed granular or protruding structures observed, indicating that a new coating layer has been successfully formed on the Ti surface and the CM coating has been successfully deposited on the titanium substrate surface. After further introducing PG on the basis of CM, the surface morphology of the CM-PG group changed again. Compared with the CM group, the surface structure of the CM-PG group is more porous, with obvious pores or encapsulation features visible in some areas, indicating that PG has been loaded onto the CM surface. The introduction of PG changed the original morphological characteristics of the CM surface, proving that the CM-PG composite coating has been successfully constructed.

[0103] Figure 10 The results of electron paramagnetic resonance (EPR) analysis of Ti, CM, and CM-PG under ultrasonic stimulation are shown, where (A) represents singlet oxygen. 1 O2 - (B) indicates the ability to produce superoxide anion·O2. - The ability to generate; (C) represents the ability to generate hydroxyl radicals ·OH; from Figure 10 The EPR results show that, under ultrasound, the CM group produced... 1 O2、·O2 - The ·OH signals in the CM-PG group were significantly stronger than those in the Ti group, indicating that CM has a strong ability to generate ROS. In contrast, the free radical signals in the CM-PG group were significantly weaker than those in the CM group, indicating that the introduction of the PG conductive hydrogel layer can suppress the generation of ROS associated with the piezoelectric system to a certain extent. This result shows that although CM has strong electroactivity under ultrasonic stimulation, it is also accompanied by obvious oxidation side reactions. The construction of the CM-PG composite system can effectively reduce ROS generation.

[0104] Figure 11 The images shown are Micro-CT three-dimensional reconstructions of bone defect areas in different treatment groups (Ti, CM, and CM-PG, and Ti+US, CM+US, and CM-PG+US with ultrasound stimulation) at 8 weeks post-surgery, as shown in Example 2. The ultrasound treatment conditions were: 1 MHz frequency, 0.2 W intensity, and 50% duty cycle for cell experiments; and 1 MHz frequency, 0.3 W intensity, and 50% duty cycle for animal experiments. Figure 11 The study revealed significant differences in new bone formation and trabecular bone reconstruction among the different treatment groups. The Ti group showed a more pronounced defect area with less new bone formation around the defect. The CM and CM-PG groups showed increased bone tissue around the defect, indicating that the surface functionalized coating can promote bone regeneration to some extent. After ultrasound stimulation, new bone formation in the defect area was further enhanced in all groups, with the CM-PG+US group showing the best performance, exhibiting more continuous bone tissue around the defect and a significantly higher degree of reconstruction than the other groups.

[0105] In summary, the structural design of the piezoelectric-conductive composite coating on the modified titanium substrate surface of this invention allows the piezoelectric charge generated by the piezoelectric material under ultrasonic stimulation to be effectively conducted and regulated by the conductive hydrogel or conductive polymer layer, reducing local charge accumulation and the resulting excessive ROS generation, thus reducing cellular oxidative stress damage. Simultaneously, the conductive hydrogel layer provides cells with a flexible, hydrophilic, and conductive interfacial microenvironment, which is beneficial for promoting the adhesion, proliferation, and osteogenic differentiation of bone marrow mesenchymal stem cells. Therefore, this invention can, while endowing titanium implants with ultrasonically responsive piezoelectric activity, improve the problems of insufficient charge conduction, ROS-induced oxidative stress, and poor cell interface adaptability in existing piezoelectric coatings, thereby enhancing the bone repair performance and osseointegration capacity of titanium implants.

[0106] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A composite coating material, characterized in that, The composite coating material includes: a surface-modified titanium substrate; and a piezoelectric layer and a conductive hydrogel layer disposed on the surface-modified titanium substrate; The conductive hydrogel layer comprises conductive filler and hydrogel.

2. The composite coating material according to claim 1, characterized in that, The mass-to-volume ratio of the conductive filler and the hydrogel matrix is ​​(95~110) μg: 1 mL.

3. The composite coating material according to claim 1, characterized in that, The thickness of the piezoelectric layer is 100 nm to 10 μm.

4. The composite coating material according to claim 1, characterized in that, The thickness of the conductive hydrogel layer is 10 μm to 200 μm.

5. The composite coating material according to any one of claims 1 to 4, characterized in that, The surface-modified titanium substrate includes a titanium substrate and micro / nano structures on the surface of the titanium substrate; the titanium substrate includes titanium or titanium alloy.

6. The composite coating material according to any one of claims 1 to 4, characterized in that, The conductive filler includes one or more of MXene-type materials, carbon nanomaterials, or conductive polymers.

7. The composite coating material according to any one of claims 1 to 4, characterized in that, The hydrogel comprises one or more of the following: cross-linked methacrylamide gelatin, gelatin, hyaluronic acid, methacrylamide hyaluronic acid, sodium alginate, polyethylene glycol diacrylate, collagen, fibroin, or chitosan.

8. The method for preparing the composite coating material according to any one of claims 1 to 7, characterized in that, Includes the following steps: Provides surface-modified titanium substrates; A piezoelectric layer is formed on the surface-modified titanium substrate; A conductive hydrogel layer is formed on the surface of the piezoelectric layer.

9. A titanium implant material, characterized in that, The titanium implant material includes the composite coating material according to any one of claims 1 to 7, or the composite coating material prepared by the preparation method according to claim 8.

10. The composite coating material according to any one of claims 1 to 7, or the composite coating material prepared by the preparation method according to claim 8, or the titanium implant material according to claim 9, in medical materials.